Upaya Tuntutan Hak yang dapat Dilakukan oleh Pihak yang Berkepentingan terhadap Akta Notaris yang Cacat Yuridis - Ghansham Anand; Agus Yudha Hernoko (Faculty of Law Hang Tuah University, 2016)
The deed made by notary has the strength of perfect evidence, both in formal and material aspects. Therefore, a notary must be accountable for the accuracy of the deed formally and materially. If the deed is not made as determined by regulations, it will impact on juridical defect of the deed and on authenticity loss of it or on cancellation of it. If the comer faces a notary to formulate and write his/her action or actions into the authentic deed in accordance with the authority of the notary, and then the notary makes the deed in accordance with the comer request or desire, in this case it provide the basis that it has occurred an engagement between the comer and the notary. Therefore, in addition to the main task that the notary pours the desire or the will of the parties who require his/her services into authentic deeds, the notary also has the obligation to ensure the validity of the authenticity. Act No. 2 of 2014 and the provisions of Article 84 and 85 of Act No. 30 of 2004 on Notary governing provisions of witnesses, do not regulate the procedure of imposing sanctions on the notary, as cost replacement, compensation and interest. Similarly, the procedure of verification to cancel the notary deed or to state that the deed only has the strength of evidence as the deed under the hand.